DIMENSI SUFISTIK-FILOSOFIS IBNU AJIBAH DALAM TAFSIR AL-BAHR AL-MADID FI TAFSIR AL-QURAN AL-MAJID - Hairul, Moh. Azwar (Farabi, 2021)
This article aims to explore the philosophical dimension of Sufism in the Sufi interpretation of Ibn Ajibah's Al-Bahr al-Madid fi Tafsir al-Qur'an al-Majid. Based on the paradigm that this interpretation is a late-period Sufi interpretation, the authenticity of this interpretation methodology is questioned. To address this issue, this article uses the paradigm of the dichotomy of Sufi teachings into Sunni (practical) and philosophical Sufism, with content analysis through the exploration, selection, and classification of collected data. This study concludes that: First, methodologically, Ibn Ajibah's Sufi interpretation is consistently based on presenting the literal meaning as the main reference before reaching the inner meaning. Second, the philosophical dimension of Sufism in Ibn Ajibah's interpretation is found in the application of concepts such as fana', baqa, ittihad, and hulu.